A 6-Week School Curriculum Improves Boys’ Attitudes and Behaviors Related to Gender-Based Violence in Kenya - Keller, Jennifer; Mboya, Benjamin O.; Sinclair, Jake; Githua, Oscar W.; Mulinge, Munyae; Bergholz, Lou; Paiva, Lee; Golden, Neville H.; Kapphahn, Cynthia (Journal of interpersonal violence, 2017)
This study investigated the effects of a gender-based violence (GBV) educational curriculum on improving male attitudes toward women and increasing the likelihood of intervention if witnessing GBV, among adolescent boys in Nairobi, Kenya. In total, 1,543 adolescents participated in this comparison intervention study: 1,250 boys received six 2-hr sessions of the “Your Moment of Truth” (YMOT) intervention, and 293 boys comprised the standard of care (SOC) group. Data on attitudes toward women were collected anonymously at baseline and 9 months after intervention. At follow-up, boys were also asked whether they encountered situations involving GBV and whether they successfully intervened. Compared with baseline, YMOT participants had significantly higher positive attitudes toward women at follow-up, whereas scores for SOC participants declined. At follow-up, the percentage of boys who witnessed GBV was similar for the two groups, except for physical threats, where the intervention group reported witnessing more episodes. The percentage of boys in the intervention group who successfully intervened when witnessing violence was 78% for verbal harassment, 75% for physical threat, and 74% for physical or sexual assault. The percentage of boys in the SOC group who successfully intervened was 38% for verbal harassment, 33% for physical threat, and 26% for physical or sexual assault. Results from the logistic regression demonstrate that more positive attitudes toward women predicted whether boys in the intervention group would intervene successfully when witnessing violence. This standardized 6-week GBV training program is highly effective in improving attitudes toward women and increasing the likelihood of successful intervention when witnessing GBV.